2015
DOI: 10.1159/000373997
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese Medicine Baicalin Suppresses mESCs Proliferation through Inhibition of miR-294 Expression

Abstract: Background: Traditional Chinese herbal medicines (TCMs) have been widely used against a broad spectrum of biological activities, including influencing the cardiac differentiation from mouse embryonic stem cells (mESCs). However, their effects and mechanisms of action on ESCs proliferation remain to be determined. The present study aimed to determine the effect of three TCMs, baicalin, ginsenoside Rg1, and puerarin, on mESCs proliferation and to elucidate the possible mechanism of their action. Methods: Cell pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…These miRNAs are predicted to be related to DNA repair signaling pathway. Our recently published data revealed that baicalin inhibited ESCs proliferation with increase of cells in G1-phase and a decrease in S phase [56] ( Figure 4). Baicalin downregulates proto-oncogenes c-jun and c-fos as well as down-regulation of miR-294 expression in mESCs while overexpression of miR-294 in mESCs reverses the alterations in the mESC proliferation and the expression of c-jun and c-fos induced by baicalin.…”
Section: Baicalinmentioning
confidence: 81%
See 1 more Smart Citation
“…These miRNAs are predicted to be related to DNA repair signaling pathway. Our recently published data revealed that baicalin inhibited ESCs proliferation with increase of cells in G1-phase and a decrease in S phase [56] ( Figure 4). Baicalin downregulates proto-oncogenes c-jun and c-fos as well as down-regulation of miR-294 expression in mESCs while overexpression of miR-294 in mESCs reverses the alterations in the mESC proliferation and the expression of c-jun and c-fos induced by baicalin.…”
Section: Baicalinmentioning
confidence: 81%
“…A number of reports, including some from our laboratory, have documented the modulation of miRNAs by natural agents [52][53][54][55][56] . Since epigenetic alterations play important roles in aberrant expression of several miRNAs in cancer cells, natural agents are now being investigated for their ability to reverse these changes that will ultimately lead to inhibition of tumor growth, invasiveness and metastasis.…”
Section: Modulation Of Mirnas By Natural Agentsmentioning
confidence: 99%
“…There is growing evidence that the action of many drugs, including Chinese herbal medicine, can be mediated through regulation of miRNA expression (Wang et al, 2015;Zhao et al, 2012). As a popular Chinese herbal medicine, Danshen has been used for a long period of time to remove blood stasis and promote blood circulation (Zhou et al, 2005), which are beneficial to ischemic heart or brain diseases (Cheng, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that evaluating the efficiency of both ESCs and iPSCs in cardiac cell therapy in an in vitro analysis is currently the focus of mainstream research [7, 8], but in recent years, iPSCs have become a great alternative for the treatment of AML [9]. These cells share many similarities with embryonic stem cells (ESCs), which serve as a model to study molecular embryogenesis and have a great potential for applications in regenerative medicine [10], including multilineage differentiation and self-renewal [11]. Moreover, embryonic stem cells (ESCs) can be differentiated into cardiac myocyte-like cells [12] Both iPSCs and ESCs are easily accessible and expandable in culture and have broad developmental potential and a high capacity for reproducibly to differentiate into spontaneously beating cardiac cells in vitro [13].…”
Section: Introductionmentioning
confidence: 99%